Preparation and Characterization of Liposomal Everolimus by Thin-Film Hydration Technique - Gabriela Torres-Flores; Azucena Gonzalez-Horta; Yadira I. Vega-Cantu; Ciro Rodriguez; Aida Rodriguez-Garcia (Advances in Polymer Technology)
In 10% to 40% of the cases of coronary stent implantation, patients face in-stent restenosis due to an inflammatory response, which induces artery thickening. Everolimus, a drug that inhibits growth factor-stimulated cell proliferation of endothelial cells, represents a promising alternative to prevent in-stent restenosis. In this study, everolimus was encapsulated by a film hydration technique in liposomes by using phosphatidylcholine and cholesterol at different ratios. As the ratio of cholesterol increases, it modulates the rigidity of the structure which can affect the encapsulation efficiency of the drug due to steric hindrance. Moreover, various lipid : drug ratios were tested, and it was found that as the lipid : drug ratio increases, the encapsulation efficiency also increases. This behavior is observed because everolimus is a hydrophobic drug; therefore, if the lipidic region increases, more drug can be entrapped into the liposomes. In addition, stability of the encapsulated drug was tested for 4 weeks at 4°C. Our results demonstrate that it is possible to prepare liposomal everolimus by film hydration technique followed by extrusion with high entrapment efficiency as a viable drug delivery system.